How much is bulk concrete sheared during pumping?. (30th October 2019) - Feys, Dimitri
Highlights: The amount of shearing in the bulk concrete is affected by ηLL /μp and τ0 /μp . Mixtures with higher w/cm and with fly ash are less prone to shear-induced changes. In specific conditions, Conventional Vibrated Concrete can be sheared inside pipes. Abstract: Pumping is an efficient procedure to place concrete inside formworks. Practical guidelines have been developed to facilitate this process for over half a century, and in the last decades, a more scientific approach has been applied to study the flow behavior of concrete in pipes. With the development of self-consolidating concrete (SCC), some substantial differences in the flow patterns of SCC and pumpable conventional vibrated concrete (CVC) have been discovered. Generally, SCC is said to be sheared during pumping, while for CVC, the shearing is only concentrated in the lubrication layer and the bulk concrete flows as a plug. This paper discusses the factors affecting the shear rate in the bulk concrete, and the additional flow rate caused by shearing the bulk concrete. The discussion is based on theoretical analyses and experiments described in literature. Increasing the ratio of the viscous constant of the lubrication layer to the viscosity of the bulk concrete increases the shearing in the bulk concrete. This appears to be the case for mixtures with lower w/cm. Increasing the bulk concrete yield stress to viscosity ratio, by using less flowable concrete mixtures, increases the plug flow and thus decreases the shear rate in the bulk concrete. However, the simple distinction between SCC is sheared and CVC remains unsheared is not valid. For certain sets of parameters, CVC can be sheared as well.